Ultrafine and highly disordered Ni2Fe1 nanofoams enabled highly efficient oxygen evolution reaction in alkaline electrolyte. (February 2018) - Fu, Shaofang; Song, Junhua; Zhu, Chengzhou; Xu, Gui-Liang; Amine, Khalil; Sun, Chengjun; Li, Xiaolin; Engelhard, Mark H.; Du, Dan; Lin, Yuehe
Abstract: Nickel iron hydroxides are the most promising non-noble electrocatalysts for oxygen evolution reaction (OER) in alkaline media. By in situ reduction of metal precursors, compositionally controlled three-dimensional Nix Fey nanofoams (NFs) are synthesized with high surface area and uniformly distributed bimetallic networks. The resultant ultrafine and highly disordered amorphous Ni2 Fe1 NFs exhibit extraordinary electrocatalytic performance toward OER and overall water splitting in alkaline media. At a potential as low as 1.42 V (vs. RHE), Ni2 Fe1 NFs can deliver a current density of 10 mA/cm 2 and show negligible activity loss after 12 h stability test. Even at large current flux of 100 mA/cm 2, an ultralow overpotential of 0.27 V is achieved, which is about 0.18 V more negative than benchmark RuO2 . Both ex-situ Mӧssbauer spectroscopy and X-ray Absorption Spectroscopy reveal a phase separation and transformation for the Ni2 Fe1 catalyst during OER process. The evolution of oxidation state and disordered structure of Ni2 Fe1 might be a key to the high catalytic performance for OER. Graphical abstract: Highlights: Amorphous NiFe NFs were synthesized with facile method. Ni2 Fe NFs show excellent OER performance. The catalytic mechanism was studied.